Milet, Türkei: Die geometrische Keramik aus Altgrabungen. Publikation der Funde der Altgrabungen und Herkunftsbestimmung durch xRFA-Messungen - Krumme, Michael (e-Forschungsberichte des DAI, 2023)
The project attempts to specify the development of Miletus ceramics in the Early Iron Age (ca 1050–700 BC). At least for the Protogeometric period, Attic and other productions were certainly known in Miletus. It seems that the city was open to both the Aegean and the mainland of Asia Minor, and may have been one of several mediators for the hinterland. As for Late Geometric it is clear that a number of shape variations cohered to a conservative tradition, and that seems to apply to the hinterland as well. It is not until Late Geometric that ‚production increases, a development that can be observed in Karia as well. During the 2015 campaign archaeometrical research using a portable XRF handheld was carried out.